NUMERICAL ANALYSIS OF A HEAT EX- CHANGER: ANSYS VS SOLIDWORKS - Pezdevšek, Marko; Fike, Matej; Hren, Gorazd; Spaseski, Igor; Ščuri, Igor (Journal of Energy Technology, 2024)
In this article, three-dimensional numerical analyses are presented with the goal of investigating heat transfer and fluid flow characteristics of an un-baffled shell-and-tube heat exchanger, using Ansys CFX and SolidWorks Flow Simulation software packages. The analyses of the overall heat transfer coefficient and pressure drop values inside the shell and tubes were performed on designed meshes with similar number of elements, for various Reynolds numbers. All numerically obtained results were validated with experimental measurements from literature.